AGROFORESTRI POLA KEBUN CAMPURAN DI DESA WAREMBUNGAN KECAMATAN PINELENG PROVINSI SULAWESI UTARA - Yali Kogoya; Hengki D. Walangitan; Reinold P. Kainde (COCOS, 2017)
ABSTRACTSYSTEM AGROFORESTRI MIXTURE GARDEN IN WAREMBUNGAN VILLAGE OF SUBDISTRICT PINELENG PROVINCE NORTH SULAWESIThe purpose of this research was to describe the agroforestry pattern at Warembungan village. The methods used in this study were survey, interview, and direct observation. Data collected were analysized descriptively and presented in graphics and tables. The results showed that dominant forest tree species used in the agroforestry pattern were Nantu (Palaquium sp.) and Angsana (Pterocarpus indicus). The dominant plantation species found were cloves (Syzygium aromaticum) andcoconut (Coconusnutifera). Thedominant fruit specieswere rambutan (Nepheliumlappaceum), jackfruit (artocarpus heterophyllus), and other species included chili (Capsicum sp.), and banana (Musa sp).Key words : system agroforestry mixture garden.